THE IMPLEMENTATION OF INQUIRY-BASED TEACHING THROUGH OPEN ENDED QUESTIONS TO IMPROVE GRADE 4 STUDENTS’ MULTIPLICATION PROBLEM-SOLVING PERFORMANCE - Fransisca, Linda; Santosa, Donald Samuel Slamet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examined the implementation of inquiry-based teaching through open-ended questions to improve Grade 4 students’ multiplication problem-solving performance at Mentari Intercultural School Jakarta. The study was conducted because many students showed low engagement, limited participation, and difficulty explaining their strategies when solving multiplication problems. A Classroom Action Research design was applied through three stages: pre-cycle, Cycle I, and Cycle II. The participants were 21 Grade 4 students. Data were collected using multiplication problem-solving tests, teacher and student observation sheets, and semi-structured interviews. The results showed progressive improvement in students’ learning outcomes. The class average increased from 62.19 in the pre-cycle to 68.57 in Cycle I and 79.52 in Cycle II. Classical mastery also increased from 19.05% in the pre-cycle to 42.86% in Cycle I and 85.71% in Cycle II. Observation and interview findings indicated that students became more engaged, more confident in explaining reasoning, and more flexible in using strategies such as arrays, equal groups, repeated addition, and decomposition. The findings suggest that inquiry-based teaching supported by open-ended questions can improve multiplication problem-solving performance by promoting active exploration, reasoning, and strategy comparison.